Analisis Strategi Pemasaran Jasa Freight Forwarding Dalam Kegiatan Ekspor Pada PT. Putro Agung Transport Service: Laporan Kegiatan Kuliah Kerja Lapangan - Tiara Ratnaningrum; I Gede Wiyasa; Harsono Teguh (Jurnal Pengabdian Masyarakat, 2024)
Basically, education is useful in preparing workers before entering the workforce so that the knowledge and skills obtained are in accordance with the type of work desired. To prepare quality students who are reliable and highly capable, University 45 Surabaya competes in improving the quality of teaching and learning both in terms of facilities and infrastructure. Learning from direct experience can be implemented through Field Work Lectures (KKL). Every company, whether operating in the product or service sector, has a goal to stay alive and develop, this goal can be achieved through efforts to maintain and increase the level of profit or profit. company operations. This can be done, if companies can maintain and increase sales of the products or services they produce. By implementing an accurate marketing strategy through exploiting opportunities to increase sales, the company's position or standing in the market can be improved or maintained. In this regard, the implementation of modern marketing today has a very big role as a direct support for increasing company profits. Marketing strategy is a form of detailed plan in the field of marketing